Geomorphology, sedimentology and minimum exposure ages of streamlined subglacial landforms in the NW Himalaya, India. (30th December 2015) - Saha, Sourav; Sharma, Milap C.; Murari, Madhav K.; Owen, Lewis A.; Caffee, Marc W.
Abstract : Streamlined subglacial landforms that include drumlins in three study areas, the upper Chandra valley around Chandra Tal, the upper Spiti Valley and the middle Yunam Valley of the NW Himalaya of India were mapped and studied using geomorphic, sedimentological and geochronological methods. These streamlined subglacial landforms include a variety of morphological types, including: (i) half egg‐shaped forms; (ii) complex superimposed forms; (iii) dome‐shaped forms; (iv) inverse forms; and (v) flat‐topped symmetrical forms. Sedimentological data indicate that subglacial deformational processes are responsible for the formation of the streamlined subglacial landforms in the Chandra Tal and upper Spiti Valley study areas. In contrast, streamlined landforms in the middle Yunam Valley are the result of melt‐out and subglacial erosional processes. In the Yunam Valley study area, 11 new cosmogenic 10 Be surface exposure ages were obtained for boulders inset into the crests of streamlined subglacial landforms and moraines, and also for a bedrock surface. The streamlined landforms date to 8–7 ka, providing evidence of an early Holocene valley glaciation, and older moraines date to ∼17–15 and 79–52 ka, representing other significant valley glacial advances in the middle Yunam Valley. The subglacial landforms in the Chandra Valley provide evidence for a ≥300‐m‐thick Lateglacial glacier that advanced southeast, overtopping the Kunzum Range, and advancing into the upper Spiti Valley. The streamlined subglacial landforms in these study areas of the NW Himalaya highlight the usefulness of such landforms in developing glacial chronostratigraphy and for understanding the dynamics of Himalayan glaciation.